ULTRASONIC CAVITATION TREATMENT OF OIL FLAX STALKS FOR THE PURPOSE OF REMOVING TECHNICAL FIBERS - YEVTUSHENKO, ARTEM; LUHOVSKYI, OLEKSANDR (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The paper considers the problems of effective extraction of bast fiber from oil flax stems with minimal energy consumption and preservation of fiber structure. The shortcomings of traditional processing methods (biological, chemical, thermomechanical), which are resource-intensive and environmentally risky, are outlined. The introduction of ultrasonic cavitation as a promising method of pre-treatment is proposed, which ensures the destruction of intercellular pectin, hemicellulose, and lignin bonds without the use of chemical reagents.An analysis of various types of ultrasonic systems—local probe, axial, and surface bath—was carried out, revealing their design limitations and uneven impact. The most effective is a tubular ultrasonic cavitator with a radial mode of oscillation, which creates a symmetrical cavitation field and evenly covers the raw material from all sides. Due to its design features (knife-like transformer sections, length less than half a wavelength), it ensures stable vibrations and uniform processing even of stems with varying diameters.The system, powered by a powerful generator with feedback, operates in automatic frequency tuning and power stabilization mode, which allows you to obtain clean fiber without loss of strength. Analysis of the principle of operation of a tubular ultrasonic cavitator with radial mode vibrations confirms its suitability for the effective extraction of bast fiber from oil flax stems. It is recommended that further experimental studies using this installation be directed toward optimizing the operating parameters—frequency, oscillation amplitude, treatment duration, and temperature regime—in order to achieve maximum fiber yield while maintaining its strength and purity.
Keywords: oil flax; primary processing; ultrasound; cavitation